School Violence Among Undergraduate Students in Kwara State: Implications for Counselling - Rahmat Tinuke Kamaldeen; Haruna Ibrahim; Suwaibah Iyabo Giwa (Jurnal Pedagogi dan Pembelajaran, 2023)
School violence has recently emerged as a widespread scenario and a primary concern globally. In Nigeria, hardly a day goes by without official or unofficial reports of some form of violence occurring in schools and manifesting in various forms, such as bullying, shootings, sexual harassment, kidnapping, and many others. Several studies show that violence in schools has a real impact on student's physical and mental health and academic achievement. Therefore, this study focuses on school violence among undergraduate students in Kwara State and its implications for counseling. This research is included in qualitative research. The type of research used is library research or literature study. The techniques used to collect data are observation and documentation. The technique used to analyze data is qualitative descriptive analysis. The results of the research are that the presence of violence has a significant impact on the field of education. Violence in educational institutions becomes an obstacle to achieving teenagers' dreams. The influence of peer groups has a significant influence on student behavior, particularly drug and alcohol use, incidents of rape and sexual harassment, involvement in examination malpractice, and reduced motivation to study.